Covid-19 2022
DOI: 10.1370/afm.20.s1.2771
|View full text |Cite
|
Sign up to set email alerts
|

PPE portraits: Patient and clinician experiences at a COVID-19 testing site

Abstract: Context: The COVID-19 pandemic mandated personal protective equipment (PPE) in healthcare settings, obscuring clinician faces and expressions, and depersonalizing patient care experiences. PPE Portraits (affixing a clinician's photo to the front of PPE) was first introduced in 2015 during the West Africa Ebola epidemic, and has been shown to help maintain patient-provider connection at times when patients may be fearful, isolated, and unable to identify clinicians caring for them. Objective: To evaluate patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…PPC serves as an example of how highly accessible online platforms can be incorporated into institutional logistics and workflows to maximize efficiencies of scale, save time, and increase the impact of healthcare initiatives, all while limiting contact and respecting infection control regulations during a pandemic. It also demonstrates how simple medical art interventions can have a measurable and large-scale impact on patients and HCWs, especially given the fear experienced by patients; one study showed that 66% and 18% of patients going to a drivethrough COVID-19 testing centre experienced moderate and severe levels of fear respectively [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPC serves as an example of how highly accessible online platforms can be incorporated into institutional logistics and workflows to maximize efficiencies of scale, save time, and increase the impact of healthcare initiatives, all while limiting contact and respecting infection control regulations during a pandemic. It also demonstrates how simple medical art interventions can have a measurable and large-scale impact on patients and HCWs, especially given the fear experienced by patients; one study showed that 66% and 18% of patients going to a drivethrough COVID-19 testing centre experienced moderate and severe levels of fear respectively [7].…”
Section: Discussionmentioning
confidence: 99%
“…In collaboration with Sunnybrook, a 16-question bilingual anonymous pilot survey was sent to PPE portrait recipients at a minimum of 1 month after having mailed the portraits. This survey was developed from previous research that collected data from a COVID-19 testing site [7]. AS created the first draft, received feedback from her interdisciplinary team at the Sunnybrook Health Sciences Centre, and further edits were given by AAD.…”
Section: Research Design/participants/procedures/validity/credibilitymentioning
confidence: 99%
“…Future research could use protective clothing to cover faces with different levels of initial trustworthiness to investigate the role of facial information in trustworthiness judgments. In addition, research has found that placing a portrait on the outside of protective clothing can help medical personnel connect better with the individuals in their care (Winter et al, 2022 ). Patients seemed more at ease, and the portraits fostered connection and trust, thereby reducing anxiety and fear and signaling to patients that they were being given holistic, optimal care.…”
Section: Discussionmentioning
confidence: 99%
“…However, masks and protective clothing can reduce the number of facial cues that are available as they partially cover the mouth and nose or completely cover the entire face. This may lead to decreased facial expression identification (Kotsia et al, 2008 ; Winter et al, 2022 ) and impair observers' ability to accurately identify the faces of target individuals (Carbon, 2020 ; Carragher & Hancock, 2020 ; Winter et al, 2022 ). Criminals often use facemasks for this reason.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation